Traumatic fractures as a result of falls in children and adolescents: A retrospective observational study. Issue 37 (September 2017) - Wang, Hongwei; Yu, Hailong; Zhou, Yue; Li, Changqing; Liu, Jun; Ou, Lan; Zhao, Yiwen; Song, Guoli; Han, Jianda; Chen, Yu; Xiang, Liangbi
Abstract : Abstract: The aim of this study is to investigate the incidence and pattern of traumatic fractures (TFs) as a result of falls in a population of children and adolescents (⩽18 years old) in China. This was a cross-sectional study. We retrospectively reviewed 1412 patients who were children and adolescents with TFs as a result of falls admitted to our university-affiliated hospitals in China from 2001 to 2010. Etiologies included high fall (height ≥2) and low fall (height <2 m). The incidence and pattern were summarized with respect to different age groups, year of admission, etiologies, genders, and the neurological function. This study enrolled 1054 males (74.6%) and 358 females (25.4%) aged 10.8 ± 4.7 years. The etiologies were low fall (1059, 75.0%) and high fall (353, 25.0%). There were 2073 fractures in total and 92 patients (6.5%) presented with multiple fractures. The most common fracture sites were upper extremity fractures in 814 patients (57.6%) and lower extremity fractures in 383 patients (27.1%), followed by craniofacial fractures in 233 patients (16.5%). A total of 231 (16.4%) patients suffered a nerve injury. The frequencies of early and late complications/associated injuries were 19.5% (n = 275) and 9.2% (n = 130). The frequencies of emergency admission, nerve injury, spinal fracture, lower extremity fractures, craniofacial fracture, sternum and rib fracture, and early complications/ASOIs were significantly larger in high fall than low fall (all P  <.001, respectively). The frequencies of medical insurance rate ( P  = .042) and upper extremity fractures ( P  <.001) were significantly larger in low fall than high fall. The frequencies of spinal fracture ( P  = .039), lower extremity fractures ( P  = .048), and craniofacial fracture ( P  = .041) were significantly larger in female than the male patients. The frequency of upper extremity fractures ( P  <.001) and the mean age ( P  <.001) was significantly larger in male than female patients. The frequencies of emergency admission, high fall, spinal fracture, and craniofacial fracture were significantly larger in patients with nerve injury than other patients without nerve injury (all P  <.001, respectively). Low falls and upper extremity fractures were the most common etiologies and sites, respectively. High fall, spinal fracture and craniofacial fracture were risk factors for nerve injury. Therefore, we should focus on patients who were caused by high fall and presented with spinal and craniofacial fracture to determine the presence of a nerve injury so that we can provide early, timely diagnosis and targeted treatment to children.